Affluence of Yogic Practices on Competition Anxiety among College Women: The impact of yogic practices on competition anxiety among college women (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was designed to examine the effect of yogic practices on competition anxiety among college women students. For the present study, thirty women students from various Departments at Annamalai University were selected as subjects. They were divided randomly into two equal groups consisting fifteen subjects. Group I underwent yogic practices for five days per week for twelve weeks. Group II acted as control which did not undergo any special training program apart from their regular program. Competition anxiety was the selected criterion variable for the present study. The subject of both the groups were administered with tests both pre and post training program. It was decided to analyse the data obtained by the statistical tool analysis of covariance to find out if there existed any significant difference at 0.05 level of confidence for the ‘F’ ratio obtained by analysis of covariance. The results of the study showed that there was a significant difference among yogic practices group and control group on competition anxiety. And also the results of the study showed that there was a significant reduction on competition anxiety due to twelve weeks of yogic practices.